Algorithm of imitation modeling of мрзс-05 on the base of petri networks usage - Варченко, О.І.; Смойловська, Ю.А.; Дідковська, М.В. (Proceedings of National Aviation University, 2010)
On the electric devices of the electric stations of the power systems, in electric networks, on electric equipment of users there can be a damage and crackpot modes. In this connection the automatic devices of defence of the system and her elements from the hazard effects of damages and crackpot modes are created and used. The article of research in the scientific publication is a microprocessor device of defence, automation, control and management of connections of 6−35 kV of МРЗС-05. A purpose of scientific publication is creation of imitation model of device МРЗС-05 on the basis of Petri networks usage for her further using for creation of virtual simulator of МРЗС-05. A мethod of imitation modeling of the relay protection system is use the theory of Petri networks. In the scientific publication an analysis of algorithm of operation of block of acceleration is shown as an example of analysis conducted for all blocks of МРЗС-05. The algorithm of operation of block of acceleration is created for creation of virtual imitator of block. It is marked, that the imitation modeling of the systems of relay defence allows to optimize losses, define the currents of short circuits, define transients, estimate the state of basic electric chain, estimate indexes of reliability. It is established, that using of algorithm of Petri networks for the modeling of operation of МРЗС- 05 and further analysis of this network consists in the receipt of important information about a structure and dynamic conduct of the modeling system. Estimation of the modeled system and producing of suggestions in relation to her improvement is carried out on the basis of this information.